The USSR and Cold War Legacy: Implications for the Current International Agenda - Michael A. Reynolds (Международная аналитика)
Interview with Michael A. Reynolds, Director of the Program in Russian, East European and Eurasian Studies and Associate Professor in the Department of Near Eastern Studies of Princeton University, USAMichael A. Reynolds is an American historian and political analyst. His teaching and research range over the geography of the Middle East and Eurasia and covers the themes of empire, international relations, nationalism, geopolitics, ethnic conﬂ ict, and religion and culture. He is the author of Shattering Empires: The Clash and Collapse of the Ottoman and Russian Empires, 1908-1918 (Cambridge University Press, 2011), co-winner of the 2011 American Historical Association’s George Louis Beer Prize, a Financial Times book of the summer, and a Choice outstanding academic title. He is the editor of Constellations of the Caucasus: Empires, Peoples, and Faiths (Markus Weiner, 2016). Reynolds also writes on contemporary issues related to Turkey, Russia, the Caucasus region and U.S. foreign policy. His writings have appeared in The Wall Street Journal, The Los Angeles Times, Newsweek, The National Interest, and War on the Rocks, among other venues. He holds a PhD in Near Eastern Studies from Princeton and an MA in Political Science from Columbia.